Site visits in interfaith and religious studies pedagogy: Reflections on visiting a Hindu temple in central Pennsylvania - Long, Jeffery D. (Teaching theology and religion, 2018)
Site visits provide an irreplaceable learning experience to students in both religious studies and the emerging field of interfaith studies. The conceptual core of this thesis is the claim, drawn from feminist epistemology, that an embodied pedagogy - a pedagogy which engages students not only intellectually, but as embodied beings who inhabit a space, engage in physical activities, and undergo various sensory experiences - is ultimately more enriching than a pedagogy centered exclusively in the classroom. Factors that make a site visit a successful instance of embodied pedagogy include the provision of sufficient context to students in advance for them to understand and appreciate the experience, an opportunity afterward to reflect on this experience in an intentional way, ensuring the site and the community whose space it is are treated with proper respect, and ensuring that the religious sensibilities of one's students are also similarly respected.